How the Special Investment Account in Islamic Banking Offers a Solution for Fixed Profit Rate in Today's Global Challenges - Bilal Ahmed; Muhammad Mumtaz Ul Hasan; Muhammad Azhar Abbasi; Muhammad Pervaiz (CV. SPDF Harmony, 2025)
Background: Islamic banking emphasizes profit-and-loss sharing and prohibits interest (riba), with Special Investment Accounts (SIAs) serving as a key instrument for depositor participation in investment outcomes. However, the growing expectation of stable profit rates and competitive market pressures pose significant challenges to the original spirit of risk-sharing in SIAs. Aims: This study investigates how SIAs provide a structural solution to the perception of fixed profit rates in contemporary global economic uncertainties. It also examines the phenomenon of Displaced Commercial Risk (DCR), regulatory implications, and SIAs’ contribution to building a resilient and ethical financial system. Methods: A qualitative, descriptive design was adopted, utilizing a systematic literature review and thematic analysis of scholarly works published between 2007 and 2024. Sources included peer-reviewed journals, regulatory reports, and thematic studies addressing SIAs, profit distribution, and financial stability. Results: Findings reveal that although SIAs are theoretically grounded in risk-sharing, market competition often drives banks toward yield smoothing, creating a perception of fixed returns. Despite these challenges, SIAs maintain a vital link between finance and real economic activity, thereby enhancing systemic stability and offering an ethical alternative to conventional interest-based systems Conclusion: SIAs represent more than an operational tool of Islamic finance; they embody an innovative, Shariah-compliant mechanism capable of structurally addressing systemic vulnerabilities in global finance. By fostering equitable risk-sharing, SIAs reduce exposure to excessive leverage and speculative crises, thus contributing to financial resilience. For Islamic banks, transparent communication about profit variability and judicious use of reserves are crucial to balancing competitiveness with Shariah integrity. Regulators, in turn, must develop harmonized frameworks that clearly differentiate SIAs from conventional deposits and address DCR as a structural tension rather than a mere regulatory anomaly. Overall, this research positions SIAs as a transformative model that not only strengthens the credibility of Islamic finance but also offers broader lessons for fostering ethical, stable, and sustainable financial systems worldwide